Reproductive biology of the South American cycad Zamia boliviana, involving brood-site pollination - Segalla, Rosane [UNESP]; Pinheiro, Fábio; Morellato, Leonor Patrícia Cerdeira [UNESP] (Wiley, 2021)
Brood-site pollination mutualisms represent extreme levels of reciprocal specialization between plants and insects. Several studies have revealed intimate associations between cycads and their insect pollinators across different continents. However, the reproductive biology of South American cycads is still poorly understood, with limited empirical data available. Here, we investigated the plant–pollinator interactions of Zamia boliviana (Cycadales, Zamiaceae), which is distributed on savanna patches in Brazil and Bolivia. Our aim was to examine reproductive biology (strobili development and their visitors) to identify potential pollinators from the perspective of dioecy and expectations of obligatory mutualism. We monitored reproductive cohorts and registered the strobiliʼs visitors. We classified the visitorsʼ activities and described the behavior of the most active and recurring ones in both reproductive structures to ascertain the potential pollinators and their relationship with the Z. boliviana. In situ experiments were used to demonstrate efficacy in seed production. Although other insects visit the strobili, only one Coleoptera (Erotylidae: Pharaxonotha) was present seasonally. Pharaxonotha cerradensis was the single species capable of transporting pollen and developing a life cycle associated with polleniferous strobili, while concomitantly visiting ovuliferous strobili. Experimental tests associated with observational evidence in the cycad indicated brood-site pollination mutualism with the Erotylidae beetle, a potential pollinator of Z. boliviana. Our investigation confirmed a new case of obligatory mutualism between cycads and P. cerradensis in the New World. Future research on Zamia from South America should address pollination systems of this genus to better understand the ecology and evolution of plant–pollinator interactions.
Keywords: beetle life cycle; biotic vectors; dioecious plants; ecological interaction; plant–insect interactions